2013
DOI: 10.1371/journal.pmed.1001421
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Coverage in MNCH: Challenges in Monitoring the Proportion of Young Children with Pneumonia Who Receive Antibiotic Treatment

Abstract: Pneumonia remains a major cause of child death globally, and improving antibiotic treatment rates is a key control strategy. Progress in improving the global coverage of antibiotic treatment is monitored through large household surveys such as the Demographic and Health Surveys (DHS) and the Multiple Indicator Cluster Surveys (MICS), which estimate antibiotic treatment rates of pneumonia based on two-week recall of pneumonia by caregivers. However, these survey tools identify children with reported symptoms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
85
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 22 publications
4
85
1
1
Order By: Relevance
“…The reported prevalence rates for severe pneumonia (11.6%) and severe diarrhea (15.3%) are high, but consistent with estimates derived from similar questions used, for example, in Demographic and Health Surveys, 18 and reflect the sensitive but nonspecific characteristics of this method. 19 The nurse auxiliary validation study showed reasonable agreement with fieldworker interviews, allowing for the expected lower specificity of the latter. Furthermore, it is important that care is sought for sick children who-on the basis of symptoms or signs apparent to parents-may have severe pneumonia or diarrhea (and not just clinically confirmed cases).…”
Section: Discussionmentioning
confidence: 78%
“…The reported prevalence rates for severe pneumonia (11.6%) and severe diarrhea (15.3%) are high, but consistent with estimates derived from similar questions used, for example, in Demographic and Health Surveys, 18 and reflect the sensitive but nonspecific characteristics of this method. 19 The nurse auxiliary validation study showed reasonable agreement with fieldworker interviews, allowing for the expected lower specificity of the latter. Furthermore, it is important that care is sought for sick children who-on the basis of symptoms or signs apparent to parents-may have severe pneumonia or diarrhea (and not just clinically confirmed cases).…”
Section: Discussionmentioning
confidence: 78%
“…Caution must be taken in the use of suspected pneumonia as a defining factor for determining true burden of pneumonia as the term includes several false positives and as such overestimates pneumonia two to seven fold. [25] However, its use as a denominator for evaluating careseeking behaviour in large-scale studies (≥20 000 children) is appropriate and has been validated. [25] …”
Section: Discussionmentioning
confidence: 99%
“…[25] However, its use as a denominator for evaluating careseeking behaviour in large-scale studies (≥20 000 children) is appropriate and has been validated. [25] …”
Section: Discussionmentioning
confidence: 99%
“…So that, physical condition of house environment should be repaired by management of house ventilation, health counseling and improvement of health worker's capacity in handling of pneumonia among toddlers in order to prevent transmission through air to healthy toddlers. 1,2 Then for condition in relation to smoke around the house environment or outdoor, it needed special actions or strategies, such as managing straw burning that should be limited between sunset to reduce pollution level. 8 …”
Section: Discussionmentioning
confidence: 99%
“…1 Nowadays, pneumonia is one of largest causes of child mortality, especially in newborn period. 2 So that, World Health Organization (WHO) in cooperation with United Nations Children's Fund (UNICEF) make The Integrated Management of Childhood Illness (IMCI). The aim of this activity is to decrease number of child death and illness due to diseases including pneumonia.…”
Section: Introductionmentioning
confidence: 99%